On the Approximation of Generalized Lipschitz Function by Euler Means of Conjugate Series of Fourier Series - Jitendra Kumar Kushwaha (The Scientific World Journal)
Approximation theory is a very important field which has various applications in pure and applied mathematics. The present study deals with a new theorem on the approximation of functions of Lipschitz class by using Euler’s mean of conjugate series of Fourier series. In this paper, the degree of approximation by using Euler’s means of conjugate of functions belonging to class has been obtained. and classes are the particular cases of class. The main result of this paper generalizes some well-known results in this direction.